Respuesta :
Answer:
-1 and -11
Step-by-step explanation:
1. 3(x+6)^2=75 ...divide by 3
2. (x+6)^2=25 ...take the square root of 25
3. (x+6)= -5 and 5.... subtract 6
4. -11 and -1
The solution steps of the given equation 3(x+6)² = 75 are given below
What is a quadratic equation?
A quadratic equation is an equation whose power of x is 2 and the coefficient of x should not be zero.
Given 3(x+6)² = 75 hence, steps are
⇒ ( x²+ 12x +36) = 75/3
⇒ x² + 12x + 36 = 25
⇒ x² + 12x + 11 = 0
⇒ x² +11x + x +11 = 0
By factorisation
⇒ x(x + 11) + (x + 11) = 0
⇒ (x + 11) [ x + 1] = 0
⇒ x = - 11 and x = - 1.
Hence, the solution steps have been given above.
For more information about quadratic equations.
https://brainly.com/question/1863222
#SPJ2